Mobilizing Youth for Participation in Nigerian Agricultural Transformation Agenda: A Grassroots’ Approach. - J S Lyocks, et all (Journal of Agricultural Extension, 2013)
The study examined the best approach to mobilize youth to participate in the Agricultural Transformation Agenda (ATA) of Nigeria. The study was conducted in two Agricultural Development Project zones of Kaduna State. Data for the study were collected using structured questionnaire, which was administered to 121 youths and analysed using descriptive statistics. Majority (88%) of the youth was interested in agriculture and 93% willing to participate in Agricultural Transformation Agenda. About 68% of the youths perceived that the agricultural transformation would create employment and reduce poverty among youths. Most of the respondents suggested that training and skills development centres should be established and their needs should be assessed before launching any agricultural programmes like ATA. A large number (92%) of the youths indicated readiness to participate in the transformation agenda. Therefore, it is recommended that the needs of the youth be assessed before mobilizing them for agricultural transformation agenda.